Basic immunology functions and disorders of the immune system - Abbas, Abul K.; Lichtman, Andrew H.; Pillai, Shiv (Elsevier, 2020)
This text emphasises the basic concepts and principles of human immunology. It includes review questions at the end of each chapter, key summary points throughout, and short, easy-to-read chapters